Enhancing Adolescents' Psychological Well-Being through Logotherapy-Based Psychoeducation - Nasution, Rahmi Azrina; Safitri, Raihan; Wulandini, Sahyu; Panjaitan, Rita; Radiah, Radiah; Al Jannah, Wardah; Nabila, Masayu; Aulia, Miftah; Amatulloh, Haficah; Triova, Utari; Anastasya, Yara Andita (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
The search for meaning in life is a fundamental aspect of an individual's psychological well-being. Adolescents, as individuals in the process of building their identities, often face challenges in discovering their lifes meaning. This study aims to examine the effectiveness of a psychoeducation program based on logotherapy (meaning-centered therapy) in enhancing students' understanding of lifes meaning and its impact on happiness and self-confidence. This study employs a quasi-experimental method with a pretest-posttest design without a control group. The research sample consists of students from SMP Negeri 7 Sawang, selected using the purposive sampling technique. The psychoeducation program was conducted through lectures, discussions, and reflections on lifes meaning, with evaluations carried out using a meaning-in-life scale instrument. The results indicate a significant increase in students' understanding after participating in the psychoeducation program. Students who previously had a low understanding of lifes meaning showed improved scores after the intervention and demonstrated more positive and confident attitudes. The conclusion of this study is that the logotherapy-based psychoeducation program effectively enhances students' understanding of lifes meaning. The implications of this study suggest that similar interventions can be integrated into school curricula to support students' psychological well-being. Future research is recommended to use a larger sample and consider experimental methods with a control group.